A Biobehavioral Perspective on Depressive Symptoms in Patients with a Cerebral Astrocytoma - Starkweather, Angela (2011)
Over 51,000 individuals are diagnosed with a primary brain tumor in the United States each year, and for those with the most common type of malignant tumor, an astrocytoma, almost 75% will die within five years of diagnosis. While surgery, radiation, and chemotherapy have improved length of survival, mortality remains high, which underscores the need to understand how other factors affect the disease trajectory. Several recent studies have shown that depressive symptoms are independently associated with reduced quality of life and survival time after controlling for medial variables in patients with an astrocytoma. Thus, depressive symptoms represent a significant risk factor for adverse outcomes in this patient population. A growing body of evidence indicates that depressive symptoms are linked to underlying biological phenomena, particularly inflammatory activation modulated through increased peripheral levels of proinflammatory cytokines. Recent research has shown that neoplastic astrocytes respond to elevated proinflammatory cytokine levels by secreting immune mediators within the central nervous system, including cytokines and glial fibrillary acidic protein (GFAP) that promote astrogliosis and angiogenesis, and may increase tumor growth and metastasis. However, because these biological factors have not as yet been measured in conjunction with depressive symptoms in these patients, little is known about the interactions that potentially influence the treatment trajectory. In order to guide future research and provide a deeper understanding of the factors that may influence depressive symptoms and length of survival in patients with an astrocytoma, a review of the literature was undertaken. Publications over the past ten years were analyzed to examine the theoretical models and measures of depressive symptoms used in previous research. While numerous studies have documented the relationship between depression and reduced length of survival, there were several methodological concerns identified and there were no studies which included biological variables. Yet, research in the basic sciences provides compelling evidence of specific neuroendocrine-immune interactions orchestrated by astrocytes that can cause depressive symptoms and alter the tumor microenvironment so that standard treatments are not as effective. These findings support the need for clinically-based research so that we can begin to understand the potentially modifiable biobehavioral mechanisms underlying depressive symptoms in patients with an astrocytoma. Grounded in the biobehavioral research paradigm of psychoneuroimmunology, a novel research program is presented that may provide a new level of understanding regarding the high prevalence of depressive symptoms in patients with an astrocytoma and lead to new treatment strategies, with possible implications for improved symptom management and quality of life in patients with brain tumors.